Exonuclease-III assisted specific target recognition cooperating with primer exchange reaction for sensitive and label-free microRNA detection - Xiaoqin Fu; Xiaoyan Fu; Didi Wu; Yunyao Lu (Journal of Analytical Science and Technology)
Abstract MicroRNAs (miRNAs) play a crucial regulatory role in biological processes and are closely associated with disease progression. The accurate identification of miRNA biomarkers holds significant potential for early disease diagnosis and therapeutic intervention. In this study, we developed a highly sensitive and label-free method for detecting miRNA-21, a well-established cancer biomarker, by combining exonuclease III (Exo-III)- assisted target recycling with primer exchange reaction (PER). Initially, the target miRNA hybridizes with the probe complex (PC), forming a blunt-end structure that is recognized and cleaved by Exo-III. Through Exo-III-mediated recycling, the released PER template binds to primer-conjugated magnetic beads (primer@MBs), initiating a polymerase-assisted PER amplification process. This reaction generates a substantial number of G-quadruplex sequences, which subsequently bind to thioflavin T (ThT), leading to a dramatic enhancement in fluorescence signal for miRNA-21 detection. The proposed method achieves an exceptionally low detection limit of 2.03 fM while maintaining high specificity for miRNA-21. Furthermore, the integration of magnetic bead (MB)-based enrichment and separation significantly reduces interference from nonspecific molecules, thereby enhancing the assay’s stability and reproducibility. Owing to its label-free design, high sensitivity, and selectivity, this approach offers a robust and versatile platform for the early detection of various disease-related biomarkers.